Bagaimana Teknologi Informasi Memoderasi Pengaruh Kompetensi Auditor dan Tekanan Waktu Terhadap Kualitas Audit - Arip Budianto; Amrie Firmansyah (Politeknik Ganesha Medan, 2025)
In carrying out its audit duties on the management and responsibility of state finances, Badan Pemeriksa Keuangan (BPK) is required to continue to improve the quality of its audits in to maintain public trust. This study aims to examine the effect of auditor competence and time pressure on audit quality and to determine whether information technology moderates the effect of auditor competence and time pressure on audit quality. The data used in this study is a questionnaire survey distributed to respondents during November to December 2023. The respondents in this study were carried out using purposive sampling with the criteria being an auditor at the BPK. The final sample used in this study amounted to 34 observations. The results showed that competence has a positive effect on audit quality, time pressure has no effect on audit quality, and information technology does not moderate the effect of competence and time budget pressure on audit quality.